Boosting power output of a sugarcane bagasse cogeneration plant using parabolic trough collectors in a feedwater heating scheme. (15th September 2015) - Burin, Eduardo Konrad; Buranello, Leonardo; Giudice, Pedro Lo; Vogel, Tobias; Görner, Klaus; Bazzo, Edson
Highlights: CSP is proposed to increase the capacity factor of existing cogeneration plants. Solar feedwater heating is an alternative in sugarcane bagasse cogeneration plants. Off-season operation is achieved as a consequence of solar feedwater heating. Hybridized plant's off-design operation was identified as solar load was increased. Abstract: This work aims to evaluate the integration of a parabolic trough solar field in a feedwater heating scheme with a sugarcane bagasse plant located in Brazil. The sugarcane facility is equipped with a cogeneration cycle that uses a regenerative feedwater heating system. Superheated steam is expanded in parallel in a back-pressure (BPST) and in a condensing-extraction (CEST) steam turbine. Solar integration was evaluated to displace the high pressure steam extraction of CEST by preheating feedwater. The hybridized plant was operated in a fuel economy mode to save bagasse during the harvest period (April to December). The economized bagasse was then used to provide the operation of power plant during the off-season. The off-design operation of solar aided plant was here identified considering minimal modifications on the existing infrastructure. As main results, bagasse economy potential due to hybridization as well as the Levelized Cost of Electricity (LCOE) of additional electricity produced was identified.